Relative compaction, physical properties and crop yield in Oxisol and Alfisol - Suzuki, Luis Eduardo Akiyoshi Sanches; Reichert, José Miguel; Reinert, Dalvan José; Lima, Cláudia Liane Rodrigues de (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate soil physical parameters and soybean (Glycine max) and black bean (Phaseolus vulgaris) yields as affected by the degree of compactness of an Oxisol and Alfisol. For the two soils, soil macroporosity, soil penetration resistance (PR), degree of compaction (DC), height and yield of the crops were determined, while for Alfisol saturated hydraulic conductivity (Kqs) was also evaluated. As the DC increases, there is a linear reduction in macroporosity and in Kqs and an increase in PR. Values of DC corresponding to the critical values of macroporosity and PR depend on soil. In the Oxisol, critical values of macroporosity and PR are reached with a smaller DC than in the Alfisol. An intermediate DC in the Oxisol is favorable to the soybean, and the optimum DC for soybean is 86%. To define an optimum DC for soybean and black bean in the Alfisol was not possible due to high levels of soil compaction in this soil.